Energy efficient adaptive message transmission algorithm for wireless sensor networks - Li, G.L.; Li, J.Z.; Guo, L.J. (Journal of Digital Information Management, 2006)
An energy efficient adaptive message transmission algorithm is proposed to save the energy consumption of the wireless sensor networks when answering the event-based ad hoc query. Compared with other algorithms based on either active or inactive message transmission mode, our adaptive algorithm emphasizes that every event lasts for a period of time, in which the ratio between the query frequency and the data production frequency changes from time to time, so using only one kind of message transmission mode is not enough to save energy. Our algorithm can adaptively change the message transmission mode for the sensor nodes according to this ratio. Experimental results showed that our adaptive algorithm could save more energy than other algorithms.
Keywords: Adaptive message transmission; Data management for wireless sensor networks; Energy efficiency; Event-based ad hoc query processing